Determination of the Difference Between Men and Women Anthropometry Auricles Using Photogrammetric Method in Sundanese Ethnic Group - Boesoirie SF; Handayani R; Gatera VA; Aroeman NA; Boesoirie TS (Dove Medical Press, 2022)
Shinta Fitri Boesoirie,1 Riri Handayani,1 Vesara Ardhe Gatera,2,3 Nur Akbar Aroeman,1 Thaufiq Siddiq Boesoirie1 1Department of Otorhinolaryngology-Head and Neck Surgery Faculty of Medicine Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 2Department of Pharmacy and Health Sciences, Universiti Kuala Lumpur - Royal College of Medicine Perak, Ipoh, Perak, Malaysia; 3Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Vesara Ardhe Gatera, Department of Pharmacy and Health Sciences, Universiti Kuala Lumpur - Royal College of Medicine Perak, Ipoh, Perak, 30450, Malaysia, Tel +605 243 2635, Fax +605 2543 6634, Email vesara.ardhe@unikl.edu.myAbstract: Auricle is one of the features that determine the face appearance. Furthermore, its shape and size are influenced by age, gender, and ethnicity. Knowledge of the normal dimensional shape, ear growth patterns, and deformity is important in diagnosing various congeital disorders. The auricle dimensions data in the Deutro-Malay population are still unavailable, specifically for the Sundanese ethnic group.Purpose: To determine the anthropometry of adult auricles in the Sundanese population.Patients and Methods: This was a quantitative descriptive study with a cross-sectional approach. The subjects used were Sundanese aged 18- 65 years old who visited the Otorhinolaryngology-Head and Neck Surgery outward at Dr. Hasan Sadikin Hospital, Bandung. Their data were obtained by photogrammetric techniques from the results of the ear photographs captured, which were then measured with ImageJ 1.48 software, and analyzed using descriptive statistics.Results: The mean value of seven anthropometric parameters of Sundanese auricle were as follows: For men, auricle length = 6.29 cm ± 0.47, auricle width = 2.95 cm ± 0.26, auricle floor = 4.71 cm ± 0.49, lobule length = 1.90 cm ± 0.24, lobule width = 1.83 cm ± 0.22, concha length = 2.74 cm ± 0.17, and concha width = 1.43 cm ± 0.15. Meanwhile in women, auricle length = 6.09 cm ± 0.42, auricle width = 2.88 cm ± 0.25, auricle floor = 4.58 cm ± 0.47, lobule length = 1.95 cm ± 0.27, lobule width = 1.82 cm ± 0.21, concha length = 2.57 cm ± 0.21, and concha width = 0.42 cm ± 0.19.Conclusion: In Sundanese ethnic, auricle length, width, and floor, as well as concha length of men tended to be greater than women. However, the women's lobule length was longer compared to men's, while the lobule and concha width tended to be the same.Keywords: anthropometry, auricular, photogrammetry, Sundanese